Frequency of television viewing and association with overweight and obesity among women of the reproductive age group in Myanmar: Results from a nationwide cross-sectional survey - Gupta, Rajat Das; Sajal, Ibrahim Hossain; Hasan, Mehedi; Sutradhar, Ipsita; Haider, Mohammad Rifat; Sarker, Malabika (BMJ Open, 2022)
This article was published in the BMJ Open [© Author(s) (or their employer(s)) 2019. Re-use permitted under CC BY. Published by BMJ. ] and the definite version is available at: http://dx.doi.org/10.1136/bmjopen-2018-024680 The Journal's website is at: https://bmjopen.bmj.com/content/9/3/e024680.full